IS THE SAND ALIVE? POSTHUMAN EXPERIMENTATION WITH/IN SOUTH AFRICAN EARLY YEARS TEACHER EDUCATION - Murris, Karin; De Souza, Luzia Aparecida; Da Silva, Heloisa [UNESP]; Reynolds, Rose-Anne (Taylor & Francis, 2022)
In this chapter, we “stay with the trouble”. We stir up, disturb and trouble educators’ reliance on the natural sciences as the only source of truth when teaching science concepts, such as ‘alive’ and ‘dead’. Within the context of Foundation phase teacher education in South Africa, we enquire into these questions as part of a transdisciplinary approach to higher education teaching, and draw on our observations and experiences of a series of sessions with the students, both inside and outside the university classroom. The question at the centre of our enquiry is posed by the teacher educator, ‘Is the sand alive?’ and what opportunities this presents for the student teachers. Karen Barad’s agential realism provides insight into how concepts are material-discursive practices and are entangled with matters of scale. With the help of Vinciane Despret’s methodological animism and Anna Tsing’s story-telling as method, we de(con)struct the concepts ‘alive’ and ‘dead’ as binary opposites, thereby enabling a philosophical education and the troubling of sharp distinctions between science, philosophy and religion.